MOTIVATIONAL FACTORS THAT INFLUENCE RETENTION OF NURSING FACULTY IN KIAMBU NURSE TRAINING INSTITUTIONS - Wanja, Susan Nyambura; Mwaura, Dr.Wanja (Journal of Health, Medicine and Nursing, 2018)
Purpose: The main purpose of this study was to establish the motivational factors that influence retention of nursing faculty in Kiambu County. Methodology: The study design was descriptive cross-sectional. The study population comprised nursing faculty currently working in Nursing Council of Kenya registered Institutions in Kiambu County. The total population of full time nurse educators in the 7 NCK registered schools in Kiambu County was approximately 50. Census sampling method was used where the entire nursing faculty in Kiambu County. The study used questionnaires to collect the required data. Descriptive statistics was used mainly to summarize the data. SPSS was used for analysing complex data. Data presentation was through the use of pie charts, and frequency tables. Results: The study findings revealed that there was a significant relationship between the effect of career development opportunity and the period of time the faculty had worked in the current organization. Availability of human resources was cited by 50% of the respondents as the work environment factor requiring improvement. Majority (66.7%) of the respondents said management of their respective institutions was not responsive to the faculty's needs. There was no significant relationship (P=0.081) between the academic status of the respondent and the effect of institutional management factors on motivation. Policy recommendation: The study recommended that a research exploring the intrinsic factors that motivate faculty in Kiambu County Nursing Institutions needs to be carried out and the institutional management of Kiambu County nursing programs should institute a system of continually finding what the faculty needs are and responding to these needs.